Extinction Phenomena: A Biologic Perspective on How and Why Psychoanalysis Works - Brakel, Linda A. (Frontiers in Psychology, 2011)
This article presents the view that much of the success of classical psychoanalysis is centrally predicated on its biological potency; focusing not on neuropsychology, but on the biology of conditioning. The argument suggests that features of classic psychoanalytic technique–the couch, meetings several times per week with both parties present, and free association–uniquely facilitate intense transferences of various sorts, and that these in turn constitute the multiple and diverse extinction trials necessary to best approximate extinction.